Professional Commitment and Machiavellian Personality on Whistleblowing Intentions - Dwi Suhartini; Rizdina Azmiyanti; Sofie Yunida Putri (Nusantara Science and Technology Proceedings, 2022)
This study was conducted to find out how the response of an individual when there is fraud in their environment. The research method used is a literature review; a search will be carried out regarding what responses are carried out when fraud occurs and if there is any intention to disclose the fraud (whistleblowing intentions). Then, find out what factors influence Whistleblowing Intentions. Using the Google Scholars search engine, the keywords used are “professional commitment on fraud”, “whistleblowing intention”, and “machiavellian”. Based on these keywords, this study will be reviewed about five articles. The research results show that an individual aware of fraud will not quickly or voluntarily disclose the fraud. Several factors influence individuals to voluntarily disclose fraud, one of which is the existence of a high professional commitment to their work. In addition, other factors exist in humans, known as Machiavellian traits. Individuals who have Machiavellian traits will instinctively prioritize their interests so that if the disclosure of fraud provides benefits for them, they will not hesitate to disclose it and vice versa. In further research, it may be possible to find out what other factors can influence a person not to hesitate to disclose fraud (whistleblowing) in the surrounding environment.